2014
DOI: 10.3390/ijms15010670
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polymorphisms of Exon 2 of the Growth Hormone Gene with Production Performance in Huoyan Goose

Abstract: Primers based on the cDNA sequence of the goose growth hormone (GH) gene in GenBank were designed to amplify exon 2 of the GH gene in Huoyan goose. A total of 552 individuals were brooded in one batch and raised in Liaoning and Jiangsu Provinces, China. Single nucleotide polymorphisms (SNPs) of exon 2 in the GH gene were detected by the polymerase chain reaction (single strand conformation polymorphism method). Homozygotes were subsequently cloned, sequenced and analyzed. Two SNP mutations were detected, and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Previous studies had shown that the polymorphisms of the avian GH gene can be identified not only at intron 2. Polymorphisms in exon regions of this gene were detected, among others, in ducks (CHANG et al 2012) and geese (ZHANG et al 2014). Meanwhile, polymorphisms in intronic regions of the avian GH gene were found in chickens at intron 1 (GHELGHACHI et al 2013), at intron 2 in ducks (WU et al 2012), at intron 3 in geese (ZHAO et al 2008) and chicken , but also at intron 4 in chickens (NIE et al 2002).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies had shown that the polymorphisms of the avian GH gene can be identified not only at intron 2. Polymorphisms in exon regions of this gene were detected, among others, in ducks (CHANG et al 2012) and geese (ZHANG et al 2014). Meanwhile, polymorphisms in intronic regions of the avian GH gene were found in chickens at intron 1 (GHELGHACHI et al 2013), at intron 2 in ducks (WU et al 2012), at intron 3 in geese (ZHAO et al 2008) and chicken , but also at intron 4 in chickens (NIE et al 2002).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the GH gene is highly polymorphic in a variety of livestock animals. Many polymorphisms have been identified in the GH gene of pig (WENJUN et al 2003), bovids (LUCY et al 1993), goat (MALVEIRO et al 2001) and poultry (SHENG-HAI et al 2007;GHELGHACHI et al 2013;ZHANG et al 2014). In ducks, the effect of GH gene polymorphism on important economic traits has been noted (WU et al 2012;.…”
mentioning
confidence: 99%
“…Next generation sequencing was performed using reduced representation (RR) sequencing from a DNA pool to detect 2188 SNPs for Barnacle goose [45]. Using the candidate gene approach, two SNPs in exon two of the growth hormone gene were detected in Huoyan goose by genotyping 552 individuals using polymerase chain reaction [46]. Using restriction site associated DNA of two DNA pools, 139,013 SNPs related to egg laying in Yangzhou goose were discovered [16].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, at the same age, a larger knob indicates greater closeness to maturity and better meat quality (Weng et al, 2021;Razmaitė et al, 2022). Hence, investigating the relationship between knob formation and production performance is of practical significance for harnessing and maximizing the potential of this trait, ultimately contributing to the growth and promotion of goose meat consumption (Zhang et al, 2014;Liu et al, 2019;Ni et al, 2022). The dimensions of the knob are predominantly determined by the breed, age, and sex of geese, as well as by various other factors (Mawdesley-Thomas et al, 1967;Wright et al, 2012).…”
Section: Introductionmentioning
confidence: 99%